Costimulatory Molecules CD80/86 Trigger Non-Specific Cytotoxic Cell of Nile tilapia (Oreochromis niloticus) to Kill CIK Cells - Yu Huang; Zhengsi Chen; Ruitao Xie; Kwaku Amoah; Bei Wang; Jia Cai; Yishan Lu; Jichang Jian (Fishes, 2022)
The teleost non-specific cytotoxic cell (NCC), as the evolutionary precursors of NK cells, is an important cytotoxic cell population in the innate immune system of teleost. We have recently realized that costimulatory CD80/86 have conservation in structural and interactional features with its ligand CD28 in Nile tilapia (Oreochromis niloticus). However, the ability of CD80/86 to regulate NCC activity has not been fully investigated. In the present study, we first obtained the recombinant fusion CD80/86 protein from O. niloticus (rOn-CD80/86). Then, NCC incubation with rOn-CD80/86 resulted in a significant production of NCC effector cytokines, including tumor necrosis factor-alpha, cellular apoptosis susceptibility and NK-lysin. Furthermore, NCC treatment with rOn-CD80/86 could significantly improve the ability to kill kidney cells of Grass carp (CIK) and up-regulate the activities of caspase-1 and caspase-3 in CIKs. The yeast, two-hybrid assay showed that On-CD80/86 cannot directly interact with non-specific cytotoxic cell receptor protein-1 of O. niloticus (On-NCCRP-1). The single-cell RNA-Seq data of Nile tilapia head kidney lymphocytes analysis found On-CD28 did not exhibit expression on NCCs subsets. The above results suggest that costimulatory molecules On-CD80/86 is independent of On-NCCRP-1 and On-CD28 receptor in modulating NCC killing activity in vitro of Nile tilapia. The results also provide more insights into the mechanism of NCC activity regulation.